Comparison of Water Footprints for Constructed Wetlands for Wastewater Treatment using Domestic and International LCI Databases - Mi-Jin Choi; Seonghyeok Cho; Sung-Chul Kim; Jongkwan Park (대한환경공학회지)
This study conducted a Life Cycle Assessment (LCA) of a constructed wetland for wastewater treatment to compare the impact of differences between domestic and international Life Cycle Inventory (LCI) databases on water footprint results. The assessment targeted a constructed wetland with a treatment capacity of 100 tons, located in Goseong-gun, with the functional unit defined as one constructed wetland treating wastewater from a small village. The analysis focused on the environmental impacts during the construction phase, and the LCA was performed in accordance with the ISO 14040 framework. For water footprint estimation, both the national LCI database and the Ecoinvent database were utilized, with priority given to field data to ensure data quality. Due to limitations in the databases, alternative assumptions were applied for some materials. The major materials used were concrete (207,000 kg), rebar (10,473 kg), and concrete square manholes (10,318 kg). The water footprint analysis showed significant differences depending on the database used: 239 m3 H2O-eq. when using the national LCI database and 203,023 m3 H2O-eq. when using the Ecoinvent database. This discrepancy is attributed to differences in emission factors and regional data for each material. In particular, the national LCI database does not sufficiently reflect the diversity of recent industrial processes and basic flows, which may lead to distorted water footprint results. Therefore, it is necessary to improve the quality and regional representativeness of the national LCI database to enhance the reliability and applicability of the assessment results.